Putative epigenetic regulation mechanisms related to production, carcass and beef quality traits in Nelore cattle - Afonso, Juliana; Jun Shim, Woo; Figueiredo Cardoso, Tainã; Bruscadin, Jennifer Jéssica; Oliveira de Lima, Andressa; Jarles da Silva Diniz, Wellison; Silva-Vignato, Bárbara; Soares Garcia, Ingrid; Liang Andre Tan, Wei; Silva Neubern de Oliveira, Priscila; Silva Mello Cesar, Aline; Barreto Mourão, Gerson; et al. (Frontiers in Genetics, 2025)
IntroductionUnderstanding regulatory mechanisms like epigenetics can help improve beef production, carcass, and meat quality. Epigenetic states are dynamic and shaped by the environment, but due to limited studies and costly detection methods, alternative approaches are needed.ObjectiveOur aim was to identify candidate regulators linked to production, carcass and beef quality traits by describing genes putatively regulated by epigenetic mechanisms in the muscle of Nelore cattle.MethodsWe in-silico identified discordantly regulated genes (DRGs) with the TRIAGE method and rank product analysis, using gene expression. We investigated the DRGs for being known bovine transcription factors (TFs) or co-factors (TcoFs) and tested the association of SNPs harbouring the DRGs with the traits. Using public muscle ATAC-Seq and ChIP-Seq data, we found that the associated SNPs were harboured in open chromatin sections of the genome and/or on histone modification regions.ResultsWe identified 51 DRGs across the traits and provided evidence of their regulatory status. 26 DRGs are known bovine TFs. A SNP upstream of the PITX2 DRG was associated with conjugated linoleic acid (CLA), 35 SNPs within or around the BTNL9 DRG were associated with backfat thickness (BFT) and 13 of the DRGs showed a regulatory impact over at least one trait.DiscussionThe correlations identified among DRGs, differentially expressed genes and traits showed intricate relationships with various TFs and TcoFs, revealing the putative relationships of these elements with the traits. The LBX1 and HOXC10 genes are candidates with evidence to be regulators of the traits, while also being subjected to epigenetic regulation.